2019
DOI: 10.1039/c9lc00653b
|View full text |Cite
|
Sign up to set email alerts
|

Long-term flow through human intestinal organoids with the gut organoid flow chip (GOFlowChip)

Abstract: Human intestinal organoids (HIOs) have many research applications but are structurally limited with closed epithelial surfaces that limit material transport. Here, we present a fluidic device designed to establish long-term flow through HIOs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 88 publications
1
44
0
Order By: Relevance
“…Intestinal organoids or enteroids have been proposed as an alternative model system to study the molecular aspects of host-pathogen interactions, especially as they apply to the gastrointestinal tract [44][45][46][51][52][53][54][55][56][57]. This approach is built on certain virtues that organotypic systems possess, including that they are untransformed and human, heterocellular [58][59][60], grow in three dimensions [46], ability to engineer "enhancements" such as co-culture with immune cells [61], flow in one direction [62], and vasculature [63] that undergo physiologic responses to stimuli such as fluid secretion [51, 64,65], mucus production [45], and innate immune responses [56,61]. In addition, researches could (i) assess all four intestinal segments from…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal organoids or enteroids have been proposed as an alternative model system to study the molecular aspects of host-pathogen interactions, especially as they apply to the gastrointestinal tract [44][45][46][51][52][53][54][55][56][57]. This approach is built on certain virtues that organotypic systems possess, including that they are untransformed and human, heterocellular [58][59][60], grow in three dimensions [46], ability to engineer "enhancements" such as co-culture with immune cells [61], flow in one direction [62], and vasculature [63] that undergo physiologic responses to stimuli such as fluid secretion [51, 64,65], mucus production [45], and innate immune responses [56,61]. In addition, researches could (i) assess all four intestinal segments from…”
Section: Discussionmentioning
confidence: 99%
“…Alterations to the HIO culture system that enable co-differentiation or co-culture of endothelium [14], neuron [17], immune or other lineages are interesting approaches to achieve a more complete model of human intestine development, and may allow enhanced maturation of cell types. Furthermore, maturation may also require perfusable vasculature [74,75], extracellular matrix alterations [10], or other mechanical inductive cues [76]. Achieving mature intestinal tissue from iPSCs in vitro remains a major challenge in the field, and continued benchmarking against multi-organ reference atlases such as the one generated here, will be required to quantify the precision of cell state specification.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the HIO epithelium produces antimicrobial peptides, which could be particularly stressful to microbes within the small, static luminal space (14). To this point, since there is no peristalsis and luminal flow within HIOs, this leads to a buildup of epithelial and microbe-derived waste within the HIO lumen (28). In this regard, technological advancements that establish steady-state liquid flow through the HIO lumen (28) may lessen or eliminate microbial stressors within the HIO microenvironment.…”
Section: Discussionmentioning
confidence: 98%